Core sampler at Ste Madeleine's Factory - (:unkn) unknown (My University, 2013)
Core sampler taking samples of sugar cane from the harvesting truck at Caroni Limited's Ste Madeleine Factory.
Cataloger's title
Keywords: Sugar factories -- Trinidad and Tobago; Sugar -- Harvesting -- Trinidad and Tobago; Sugar machinery -- Trinidad and Tobago